New Early Cretaceous species of Zonocypris G. W. Müller, 1898 (Crustacea: Ostracoda) from the Crato Formation, Brazil - Piovesan, Enelise Katia; Melo, Gustavo Dias; Cabral, Maria Cristina; Guzmán, Juliana (Zootaxa, 2022)
Two new species of Zonocypris G. W. Müller, 1898 are described from the late Aptian of the Araripe Basin, Northeast Brazil: Zonocypris berthoui sp. nov. and Zonocypris dorsoconvexa sp. nov. Species of this genus occur from the Early Cretaceous to the Holocene and are characterized by a small globular carapace, often ornamented over the whole surface by concentric ridges with simple normal pore canals, showing a remarkable morphological stability during the evolution of the genus. The first records of the genus point to an Atlantic origin. In Aptian deposits, species of Zonocypris are rare, occurring in brackish/freshwater assemblages, with marine influence.